Agile project management in South African financial service organisation: a case study - Mhlanga, Success Siphesihle (Department of Information Systems, 2026)
Financial service organisations have traditionally utilised conventional project management approaches to execute software projects. However, with the emergence of the agile methodology, there has been a growing transition among these organisations towards adopting agile project management (APM) practices. Scholars in the field have pointed out that traditional project management approaches are inadequate in meeting the dynamic demands of the financial service sector. This observation helps to explain the industry's inclination towards alternative approaches. The increasing trend of organisations embracing Agile Project Management (APM) highlights a pressing need to rethink the delivery mechanisms for software development projects. Previous studies have focused on documenting employees' experiences during an agile transition, but there is a need for further examination of the experiences of management. This study analysed the perceptions of managers in a financial service organisation during an APM transition. Utilising a case study methodology, perceptions, and experiences of 14 managers were analysed using a qualitative research paradigm. The study showed that the financial service organisation transitioned to leverage the benefits of agile such as incremental delivery, reaching the market faster, gaining visibility on the product output, and increasing transparency. The findings revealed that value was immediately created by increasing visibility and transparency, meeting customer demands, and quantifying return on investment. Some managers associated “walking the agile journey together” with the different levels of management as a positive attribute towards transitioning. The study found that executive management influenced decisions and drove change throughout the transition process. Additionally, a relationship between resistance to change and the absence of a change management plan was identified. The absence of a clear and communicated change management plan contributed to frustrations in persuasion, which resulted in some employees leaving the organisation. This study suggests that further research is needed to examine the consequences of transitioning without a change management plan.